(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2022)
The article, based on the accounting of natural fodder lands, statistics on the consumption of basic food products by the population, imports of livestock products, the dynamics of livestock numbers (cattle), analyzed their use taking into account economic, environmental and social aspects. Analyzing the data, it can be concluded that the density of cattle on agricultural land has decreased by more than eight times, which has led to a catastrophic decrease in the application of organic fertilizers and a deterioration in the quality of crop production. The decrease in the number of cattle has led to an increase in the cost of products and a decrease in their consumption. At the same time, in 2018, Ukraine imported 577517kn dollars of meat and meat products and milk and dairy products, which in equivalent amounts to more than 15.9 billion hryvnias. The cost of livestock products produced in Ukraine in 2018 amounted to 138.74 billion UAH. The efficient use of land resources is of great importance in the country’s agricultural economy. The increase in the quantity and quality of livestock products can be successfully carried out only with a significant increase in the efficiency of land use, which becomes especially relevant in modern agricultural conditions. The implementation of these measures will lead to the import substitution of livestock products and deeper processing of crop products, which will make it possible to decapitate the country’s food security. These activities will provide an opportunity to improve the social and economic situation in rural areas.